BUHAY WIKA: FOCUSED ETHNOGRAPHY ON THE EXPERIENCES OF MTB-MLE TEACHERS IN TEACHING THE AYTA MAGBUKUN LANGUAGE UNDER THE IPED CURRICULUM - Zharla Nicholle Mangalindan; Jemma Rose Dela Cruz; Grace Angela Catipay; Anne Jhanelle Sioco; Gale Ian Mateling; Espiranza Dumalaog; Nian Kris Luzano; John Harold Leano (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This focused ethnography study examined the experiences of Mother Tongue- Based Multilingual Education (MTB-MLE) teachers in teaching the Ayta Magbukun language within the framework of the Indigenous Peoples Education (IPED) curriculum. This qualitative research employed face-to- face unstructured interviews as the primary data-gathering method as well as fieldwork that involved direct engagement with MTB-MLE teachers in their teaching environments, including classroom observations. Thematic analysis was used to analyze the collected data, enabling the identification of core themes that came up from the participants' responses. In the entirety of the data collection period, strict adherence to ethical principles such as justice, beneficence, and respect for participants were observed. It was revealed that only one MTB-MLE teacher teaching Ayta Magbukun is from the Ayta community and non-Ayta teachers struggle to teach Ayta Magbukun due to a lack of skills and knowledge. There is also a lack of training for teachers on the IPEd curriculum as well as limited learning materials to aid the teaching of Ayta Magbukun. Therefore, it is recommended to increase the recruitment of Ayta Magbukun teachers in MTB-MLE programs, provide specialized training for non-Ayta teachers in the Ayta Magbukun language, strengthen training programs for teachers in the IPEd curriculum, ensure adequate support and resources for learning materials in MTB-MLE programs, and the conduct of further research with a larger participant group to strengthen findings